The Effects of Cash for Clunkers on Local Air Quality - Ines Helm; Nicolas Koch; Alexander Rohlf (Institute of Labor Economics (IZA), 2023)
We study the effects of a large car scrappage scheme in Germany on new car purchases and local air quality by combining vehicle registration data with data on local air pollutant emissions. For identification we exploit cross-sectional variation across districts in the number of cars eligible for scrappage. The scheme had substantial effects on car purchases and did not simply reallocate demand across time in the short-term. Nevertheless, about half of all subsidized buyers benefited from windfall gains. The renewal of the car stock improved local air quality suggesting substantial mortality benefits that likely exceed the cost of the policy. While policy take-up is somewhat smaller in urban districts, improvements in air quality and health tend to be larger due to a higher car density.
Keywords: H20; H23; Q53; Q58; 330; cash for clunkers; local air quality; car scrappage schemes; emissions; car rebate